Narrative-biographical Material: A Proposal for Elaboration (OMNaB) - Fabiś, Artur; Dubas, Elżbieta (Qualitative Research in Andragogy: Polish Research Experiences, 2026)
The author presents a proposal of a way of elaborating on empirical material collected through narrative-biographical interview. She takes attention to presenting the person of the narrator, selected of life history and life story analysis of research material. Aside from guidelines for elaborating on empirical material coming from one narrator, she sketches out hints for elaborating empirical material coming from narrators.